Improving Socio-Emotional Competence of Grade IV Elementary School Students by Implementing Traditional Games in Learning - Tri Widyananti; Adi Winanto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: Social-emotional competence is important in fostering children's development, because it can help children to solve problems, increase prosocial behavior, build good relationships, and adapt to increasingly large and complex demands. Aim: This research aims to improve the social emotional competence of students in class 4 of SD Negeri Kutowinangun Salatiga with social emotional learning. Method: The type of research used is Classroom Action Research. The subjects of this research were all 22 Keas IV students at SD Negeri Kutowinangun Salatiga for the 2023/2024 academic year. Result and Discussions: The research results showed a significant increase in students' social emotional competence and activeness. At the pre-cycle stage, many students are less active and unable to control their emotions well. However, through traditional implementation, there was an increase in the average score in both social emotional competence and student activity. Cycle 1 shows an increase from the very poor category to poor, while cycle 2 shows a further increase to the good category. Traditional games have proven effective in improving students' social interaction, cooperation and communication skills. Conclusions: This research shows that traditional games can be a fun and effective learning tool, helping students develop various competencies and control emotions in a relaxed and interactive atmosphere. Therefore, the research was stopped in cycle 2 because it had achieved the expected results.